Adaptation of bird hemoglobins to high altitudes: demonstration of molecular mechanism by protein engineering - Jessen, T H; Weber, R E; Fermi, G; Tame, J; Braunitzer, G (Proceedings of the National Academy of Sciences - PNAS, 1991)
Of two closely related species of geese, one, the greylag goose, lives in the Indian plains all year round, while the other, the bar-headed goose, lives at the Tibetan lakes and migrates across the Himalayas to winter in India. Another species, the Andean goose, lives in the High Andes all year round. Possession of a Hb with high oxygen affinity helps to adapt bar-headed and Andean geese to high altitudes. The Hb amino acid sequences of the bar-headed and the greylag geese differ by four substitutions, of which only one is unique among bird sequences: Pro-119 alpha (H2)---Ala. Perutz proposed that the two-carbon gap left by this substitution at the alpha 1 beta 1 contact raises the oxygen affinity, because it relaxes the tension in the deoxy or T structure [Perutz, M. F. (1983) Mol. Biol. Evol. 1, 1-28]. It was later found that the Hb of the Andean goose has a gap in the same position, due to the complementary substitution Leu-55 beta (D6)---Ser. We have tested Perutz's hypothesis by introducing each of these substitutions into human globin synthesized in Escherichia coli. The reconstituted Hbs combine cooperatively with oxygen. Their oxygen affinities exceed that of normal human Hb by an even larger factor than that found between the high-flying geese and the greylag goose. The mutant Hb Met-55 beta (D6)---Ser was crystallized. Its structure is the same as that of HbA, except in the immediate environment of the gap left by the substitution of the serine for the methionine side chain, which evidently causes the increased oxygen affinity of this Hb.